Controlling The Amendment Of The Nri Constitution And The Necessary Of The President's Service For Three Periods - Irmanjaya Irmanjaya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The constitution in Indonesia has undergone several changes since Indonesia's independence. In this dynamic, Indonesia is in the phase of finding its identity and the right government system in accordance with the conditions of the Indonesian nation. Changes to the constitution repeatedly, namely in the Post-Independence period, the 1945 KRIS, the 1950 Constitution, the New Order, the Old Order, and the Reformation. Article 7 of the 1945 Constitution of the Republic of Indonesia states that the President governs for a term of five years and can be re-elected in the election of the head of state. However, until the New Order era, the presidential term limit was not determined. Resulting in abuse of power and political chaos. The post-amendment reform era changed Article 7 by limiting the president's power to only two terms. The amendment to Article 7 is referred to as the embodiment of reform and is in accordance with the opinion of the Indonesian people so that power regeneration can occur. The discourse on the third amendment in Article 7 is pro and contra because it is planned that there will be a change in the limitation of the presidential term of office to three periods. This discourse is not in accordance with the spirit of Article 7 of the 1945 Constitution of the Republic of Indonesia and the controversy among the Indonesian people. The Indonesian people hope that the abuse of power will not repeat itself as in the pre-reform era and stick to the mandate of Article 7 of the 1945 Constitution of the Republic of Indonesia that the president is limited to two terms.